Caracterização física e química dos solos de manguezais em São Caetano de Odivelas-Pa - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2003)
Mangroves are coastal ecosystems, transitional between terrestrial and marine environments, characteristic of tropical and subtropical regions. They are an open system that maintains relationships with other environments. Their proper functioning depends on some vitally important factors, including soil stability and an adequate supply of nutrients. Considering the diversity of conditions presented in these environments, subordinated to the tidal regime, the most favorable alternatives for use and management can be established, as long as their natural resources, such as soil, are properly known. This work aimed the physical (grain size) and chemical (salinity, pH, Eh, N, P and K) characterization of mangrove soils as a contribution to the generation of pedological data that can interact with other studies for a better understanding of the functioning of these ecosystems and to subsidize their adequate management. The study was conducted in the municipality of São Caetano de Odivelas, which belongs to the coastal belt of northeastern Pará State, where 05 soil profiles (Pl, P2, P3, P4 and P5) were collected at a depth of approximately 3 meters, using a 1-m mud auger coupled with two 1-m extensions each. The morphological description of the profiles was adapted from Lemos & Santos (1996). Methods adapted from EMBRAPA (1997) were used in the preparation and analysis of the material. The soils studied are composed of unconsolidated sediments of recent formation. They present a shallow, mineral-organic horizon, followed by strongly gleyed horizons (grayish), the sequence of horizons being A and Cg, with the presence of mottling of various colors, such as: yellow-brown, bruno and bruno. The consistency varies from firm to very firm, very plastic and sticky. The other data (chemical and physical) are in progress.
Physical and chemical characterization of mangrove soils in São Caetano de Odivelas-Pa
Keywords: Solos; Manguezal; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS